2022
DOI: 10.1073/pnas.2210114119
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a saxitoxin (STX) binding code enables discovery and characterization of the anuran saxiphilin family

Abstract: American bullfrog ( Rana castesbeiana ) saxiphilin ( Rc Sxph) is a high-affinity “toxin sponge” protein thought to prevent intoxication by saxitoxin (STX), a lethal bis-guanidinium neurotoxin that causes paralytic shellfish poisoning (PSP) by blocking voltage-gated sodium channels (Na V s). How specific Rc Sxph interactions contribute to STX binding has not been defined and whether other organisms have similar prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 49 publications
1
25
1
Order By: Relevance
“…Taken together, this supports a model where Os ABG is produced in the liver, binds alkaloids present in the blood or recently absorbed by the intestines, and then may transport alkaloids to the skin for bioaccumulation. The micromolar K D value we identified for Os ABG with PTX is higher than the previously reported value for CBG [34,36], and TBG [54], as well as that reported for the “toxin sponge” protein saxiphilin [55], which are all in the nanomolar range. The lower affinity of Os ABG provides further support to the hypothesis that Os ABG may be acting as a transporter protein to other tissues, and would be in line with the hypothesis that there may be other mechanisms involved in autoresistance to circulating alkaloids not bound by protein [56].…”
Section: Discussioncontrasting
confidence: 81%
“…Taken together, this supports a model where Os ABG is produced in the liver, binds alkaloids present in the blood or recently absorbed by the intestines, and then may transport alkaloids to the skin for bioaccumulation. The micromolar K D value we identified for Os ABG with PTX is higher than the previously reported value for CBG [34,36], and TBG [54], as well as that reported for the “toxin sponge” protein saxiphilin [55], which are all in the nanomolar range. The lower affinity of Os ABG provides further support to the hypothesis that Os ABG may be acting as a transporter protein to other tissues, and would be in line with the hypothesis that there may be other mechanisms involved in autoresistance to circulating alkaloids not bound by protein [56].…”
Section: Discussioncontrasting
confidence: 81%
“…Some frogs resist STX poisoning 7 , 8 , 9 , 10 , a property attributed to high-affinity STX binding proteins called saxiphilins (Sxphs). 1 , 9 , 11 Sxph-like activity is found in arthropods, 12 amphibians, 12 , 13 , 14 fish, 12 and reptiles. 12 Except for frog and toad Sxphs 1 and a pufferfish protein, Pufferfish Saxitoxin and Tetrodotoxin Binding Protein, PSTBP, that binds STX and related toxin, tetrodotoxin (TTX), 15 the molecular origins of these STX binding activities are uncharacterized.…”
Section: Before You Beginmentioning
confidence: 99%
“… 1 , 9 , 11 Sxph-like activity is found in arthropods, 12 amphibians, 12 , 13 , 14 fish, 12 and reptiles. 12 Except for frog and toad Sxphs 1 and a pufferfish protein, Pufferfish Saxitoxin and Tetrodotoxin Binding Protein, PSTBP, that binds STX and related toxin, tetrodotoxin (TTX), 15 the molecular origins of these STX binding activities are uncharacterized. Our recent structural studies have shown that frog and toad Sxphs have a single, high affinity (Kd∼ 1 nM) STX binding site that uses an STX binding code that shares both structural and energetic binding principles with the Na V STX binding site.…”
Section: Before You Beginmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,19] Interestingly, American bullfrogs (Rana castesbeiana) are resistant to STX poisoning by producing a 91-kDa protein saxiphilin (Sxph), which binds to STX with high affinity. [20,21] Sxph is present in the bullfrogs' plasma and heart, acting as a molecular "sponge" to bind and sequester STX in the event of toxin exposure. Similar toxin resistance mechanisms have been observed in several marine animals, such as pufferfish, cockles, and crabs.…”
Section: Introductionmentioning
confidence: 99%